Association between atrial fibrillation and coronary slow flow. (14th October 2021) - Zhuang, Z.X.D; Zhang, S.Z; Liao, X.X
Abstract: Background: The relationship between arrhythmia and coronary slow flow (CSF) is unclear. We aimed to explore the association between atrial fibrillation (AF) and CSF. Method: In this cross-sectional study, we included 2, 060 participants patients from PCI-registry (NCT 02498470) who underwent coronary angiography with clinical chest pain and without significant coronary stenosis. According to coronary blood flow rate measured by the thrombolysis in myocardial infarction frame count (TFC) method, CSF was defined as TFC>27. AF was identified by ECG performed during hospitalization. We used logistic regression to assess the association between AF and CSF. Results: Among 2, 060 participants, 132 participants were diagnosed with AF. CSF rates were higher in AF group than in the control group (22.0% vs 13.9%, P=0.011). Logistic regression showed that AF was independently associated with CSF after adjustment for traditional risk factors (OR=2.06; 95%, 1.28–3.34; P=0.003). Conclusion: Our study demonstrated that AF was association with increased risk of CSF. Further studies are needed to confirm this finding and explore the potential mechanism. Funding Acknowledgement: Type of funding sources: None.